Peran Pendampingan Perguruan Tinggi Dalam Keberlanjutan UMKM: Studi Kasus Pada Uppks Matahari Kabupaten Bogor - Sutarti, Sutarti; Mulyana, Mumuh; Hermawan, Yanto; Fahsany, Donny Hendry; Herawati, Heti; Nurjanah, Yayuk (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
ABSTRACTThis study aims to identify an innovative and sustainable MSME mentoring model through community service by IBI Kesatuan lecturers. A case study at UPPKS Matahari, Bitungsari Village shows that the combination of face-to-face mentoring and the use of information technology has succeeded in increasing the capacity of MSMEs in managing their businesses independently. The mentoring program that includes training, consultation, and market access facilitation has encouraged MSMEs to develop new products and services, and improve product quality. The results of this study provide important implications for universities in designing community service programs that are relevant to the needs of MSMEs and support sustainable local economic development.Keywords: MSMEs, Universities, Sustainability.